Modeling of Tsunami Inundation Maps Along the Pacitan Coast using ComMIT 1.8.1 and Quantum GIS 2.18.28 "Las Palmas" Software: Pemodelan Peta Genangan Tsunami Di Pantai Pacitan Dengan Menggunakan Software ComMIT 1.8.1 DAN Quantum GIS 2.18.28 "Las Palmas" - Latifah, Asa; Masykuri, A. Fauzi; Khumaedi (Sunan Kalijaga Journal of Physics, 2024)
Indonesia is a maritime country located on the equator with 3 main plates, namely the Eurasian plate, the Indo-Australian plate, and the Pacific plate which is known as the Ring of Fire (Pacific ring of fire). If these plates interact along the troughs and fractures of the earth's crust which are the source of earthquakes at sea, it will trigger a tsunami. Geographically, Pacitan Regency is located between 110 55 - 111 25 East Longitude and 7 55 - 8 17 South Latitude bordering the Indian Ocean to the south and is located on the Java Megathrust which causes Pacitan to have the potential for earthquakes that cause tsunamis. That is why it needs to be studied in relation to wave height, tsunami arrival time and tsunami inundation map as measures of tsunami hazard warnings along the coast of Pacitan. The results show that the height of the tsunami waves along Pacitan Beach with the Mw 8.7 earthquake ranged from 6 meters to 13 meters with the fastest arrival time of 23 minutes. The tsunami inundation that occurs along Pacitan Beach ranges from 0.4 km to 0.7 km from the shoreline.